Evaluation Method for Thermal Conductivity in Warm Dense Matter by using Ruby Fluorescence Probe. (March 2016) - Takahashi, Takuya; Kawaguchi, Yoshimasa; Ohuchi, Takumi; Takahashi, Kazumasa; Sasaki, Toru; Kikuchi, Takashi; Aso, Tsukasa; Harada, Nob.
Abstract: We have proposed a concept of experimentally estimating thermal conductivity in warm dense matter from the ruby fluorescence. To reduce the dimension of the system, a cylindrically arranged sample tamped by the ruby capillary has been considered. From the estimated ruby temperature, in which is simulated by the time-dependent thermal diffusion in equation, the ruby fluorescence can be obtained from 0.5 mm to 0.6 mm. The results indicated that the low density regime as ρ/ρs < 0.004 is possible to evaluate the ruby fluorescence.